Influenza A Viral Infection with Septic Shock in Pregnancy - Soe, Lwin; Myat, Su Bo; May, Shi Leong; Haris Njoo, Suharjono; Tin, Moe Nwe (Hindawi Publishing, 2019)
Te infuenza virus is RNA virus and is classifed into four subtypes, infuenza A, infuenza B, infuenza C, and infuenza D. One of the subtypes of infuenza A, the H1N1 strain, also known as swine fu, is especially of high risk for development of complications in pregnant women. Te influenza A virus infection is difficult to diagnose clinically because its presenting symptoms are similar to those of the common cold but are more severe, last longer, and can be potentially life-threatening. This case also presented with common cold symptoms but her condition worsened later. Fortunately, obstetric health providers were vigilant enough to address the developing infection and its related complications. It was the cooperative effort of multidisciplinary team care which resulted in a flavourable outcome in both mother and baby.